Osteology of a perinatal aristonectine (Plesiosauria; Elasmosauridae) - O'gorman, Jose Patricio; Talevi, Marianella; Fernández, Marta Susana (Antarctic Science)
Perinatal specimens give valuable information about the first stages of vertebrate ontogeny. Here, the morphology and palaeohistology of an aristonectine perinatal specimen from Seymour Island (Isla Marambio), López de Bertodano Formation are analysed. The palaeohistological analysis shows incomplete endochondral ossification (retention of a calcified cartilaginous core in the medullary region), predominance of primary bone tissue without secondary remodelling, lack of primary or secondary osteons and of growth marks in the cortical bone, and open vascular spaces not surrounded by a thin coat of lamellar bone tissue. General lines of morphological changes were inferred from comparing the fossil with an adult aristonectine specimen indicating i) a tendency of relatively high and broad posterior cervicals to decrease during ontogeny, ii) a decrease of relative size of the dorsolateral process and an increase of the glenoid ramus and iii) the existence of two separate stages in propodial growth divided into an initial elongation followed by a distal expansion. The presence of a perinatal specimen in the James Ross Archipelago indicates that the region was used as a breeding area by the aristonectines during the last part of the Cretaceous. Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Talevi, Marianella. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Río Negro. Sede Alto Valle. Instituto de Investigaciones en Paleobiología y Geología; Argentina Fil: Fernández, Marta Susana. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina